2019
DOI: 10.1177/1527154419838630
|View full text |Cite
|
Sign up to set email alerts
|

Potential Crisis in Nurse Practitioner Preparation in the United States

Abstract: The Doctor of Nursing Practice (DNP) degree was established to expand nurse practitioner education by adding new competencies. In 2004, the American Association of Colleges of Nursing released a position statement that redefined practice from only clinical care of patients to include nonclinical care. This policy position likely contributed to the rapid growth of DNP programs. Historical background on the development of the DNP is provided. An analysis was conducted of the programs reported in the American Ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 9 publications
(9 reference statements)
0
21
0
1
Order By: Relevance
“…Nos últimos dois anos observa-se uma crescente discussão da ampliação do escopo de práticas do enfermeiro na APS para atender às necessidades de saúde frente ao envelhecimento populacional e aumento de pessoas portadoras de doenças crônicas. Todavia, este debate não está apartado do diagnóstico da falta de médicos nos serviços, num contexto de crise [4][5][6] . ____________________ I Mestre.…”
Section: Introductionunclassified
“…Nos últimos dois anos observa-se uma crescente discussão da ampliação do escopo de práticas do enfermeiro na APS para atender às necessidades de saúde frente ao envelhecimento populacional e aumento de pessoas portadoras de doenças crônicas. Todavia, este debate não está apartado do diagnóstico da falta de médicos nos serviços, num contexto de crise [4][5][6] . ____________________ I Mestre.…”
Section: Introductionunclassified
“…Nurse practitioner preparation and education may soon be in a crisis mode. In Mundinger and Carter's (2019) article, ''Potential Crisis in Nurse Practitioner Preparation in the United States,'' a timeline and analysis of the number of Doctor of Nursing Practice (DNP) programs in the United States from 2005 through 2018 showed that 85% of DNP programs since inception of the DNP degree are nonclinical. Of the 553 DNP programs, 83-or 15%-are clinically focused.…”
mentioning
confidence: 99%
“…We read with great interest Mundinger and Carter’s exposition of how, in their view, Doctor of Nursing Practice (DNP) education has lost its way and what consequences might result. In “Potential Crisis in Nurse Practitioner Preparation in the United States,” they note that the DNP arose to address the demand for more deeply skilled nurse practitioners (NPs) ready to respond proactively to a rapidly changing health care environment and the complex care needs with which patients present (Mundinger & Carter, 2019). Mundinger and Carter (2019) argue that these new NP skills were meant to be primarily clinical, yet, as of 2018, only 15% of DNP programs focus on providing advanced clinical training, while the overwhelming majority focus on administration and leadership.…”
mentioning
confidence: 99%
“…In “Potential Crisis in Nurse Practitioner Preparation in the United States,” they note that the DNP arose to address the demand for more deeply skilled nurse practitioners (NPs) ready to respond proactively to a rapidly changing health care environment and the complex care needs with which patients present (Mundinger & Carter, 2019). Mundinger and Carter (2019) argue that these new NP skills were meant to be primarily clinical, yet, as of 2018, only 15% of DNP programs focus on providing advanced clinical training, while the overwhelming majority focus on administration and leadership. Mundinger and Carter attribute the growth in this nonclinical focus to an ill-advised decision by the American Association of Colleges of Nursing (AACN) to define nursing practice to include both nonclinical and clinical care.…”
mentioning
confidence: 99%
See 1 more Smart Citation